Female control of mate plugging in a female-cannibalistic spider (Micaria sociabilis) - Sentenská, Lenka; Pekár, Stano; Lipke, Elisabeth; Michalik, Peter; Uhl, Gabriele (BMC evolutionary biology, 2015)
BACKGROUND: Sperm competition imposes a strong selective pressure on males, leading to the evolution of various physiological, morphological and behavioral traits. Sperm competition can be prevented by blocking or impeding the access to female genitalia by means of a mating plug. We investigated the factors responsible for plug production and function in the promiscuous female-cannibalistic spider Micaria sociabilis (Gnaphosidae). RESULTS: We performed mating trials using females with and without a plug that consists of an amorphous mass. The mating trials demonstrated that the probability of male plugging increased non-linearly with the duration of copulation. Copulation duration and plug production seem to be controlled by the female. We found that females terminated matings later if males were fast at genital coupling. Whereas incomplete plugs had disappeared on the day following copulation, complete plugs persisted (40%). In matings with females with complete plugs, only a small proportion of males (7%) were able to remove the plug, indicating the high effectiveness of plugging. Moreover, males ceased attempts to copulate with plugged females with higher probability. 3D X-ray microscopy of the female and male genitalia showed that the plug material can extend far into the female genital tract and that the plug material is produced by a massive gland inside the palpal organ of the modified male pedipalps. CONCLUSIONS: Our study demonstrates that the mating plug in M. sociabilis constitutes an effective male strategy to avoid sperm competition that seems to be under female control.
Keywords: Behavior, Animal; chování zvířat; Male; Genitalia, Female; Animals; kompetitivní chování; Female; ženské pohlavní orgány; ženské pohlaví; mužské pohlaví; pavouci; Copulation; kopulace; zvířata; Spiders; Competitive Behavior